(untitled) (Al-Aasar, 2025)
Urdu fiction writer Altaf Fatima is considered one of the most prominent female novelists, short story writers, translators and teachers of Pakistan. All her creative writings reflect her diverse experiences and deep observation. She was a nationalist writer. Her novels and short stories mixed both the passion for the homeland and religious flavor. She has her own style of writing which is sometimes reflected in her style and sometimes in the behavior of her characters. Most of her characters include girls and women who have deviated from the existence of society and have tried to challenge the standards and values of their families and society. While creating such characters, she kept in mind the attitudes of her society under which women were encouraged to remain subjugated in every respect with regular planning. Altaf Fatima always wrote her fiction by diving into the depths of art, which is why her fiction has a distinct creative flavor and a distinct scent. Her attitude towards intellectual and artistic matters was so careful that she completed her famous novel "Chalta Musafir" in a period of ten years. This novel is a prime example of her intellectual and artistic maturity. This novel not only has a distinct place in her own fiction, but is also considered one of the representative novels of Urdu. This article is written about the Psychological conflict of characters in her novel "Nishan-e-Mehfil".